Legal Protection For Children As Corn Shellers In Balutan Village, Bupon District, Luwu Regency South of Sulawesi, Indonesia - Suriadi Yusuf; Helmi Kamal; Fitriani Jamaluddin; Sahhamdabbar Sahham (Al-Amwal : Journal of Islamic Economic Law, 2025)
Purpose  –  This research aims to determine the practice of children as corn shelling workers in Balutan Village, Bupon District, Luwu Regency; to find out the protection for children as corn shelling workers in Balutan Village, Bupon District, Luwu Regency. Method –  The type of research used is empirical research, using a sociological approach. The source of data in this study is primary data obtained from the results of interviews with child laborers, corn sheller entrepreneurs and parents/guardians of children who work. The data collection techniques used in this study are observation, interviews, and documentation. Result –The results of this research indicate that corn shelling work involving child labor has violated the provisions stipulated by the applicable laws and regulations. Such as working hours that exceed the maximum working time limit for children, working in places with extreme temperatures for children, and no work boundaries between adult and child laborers, as well as no guaranteed work safety for child laborers. Thus, entrepreneurs who employ children as corn shelling workers in Balutan Village, Bupon District, Luwu Regency, have violated the law. Implication – As a practical implication, Child Labor Violation: The engagement of minors in corn shelling operations contravenes national labor statutes, namely those pertaining to child labor protections. Possible Legal Consequences: Entrepreneurs may incur criminal or administrative effects, such as fines or imprisonment for breaching child labor regulations. The findings underline the imperative for labor inspectors and law enforcement regulators to adopt proactive strategies in monitoring and enforcing compliance